Challenging the hegemon: great power motives for Russia’s struggle with the US over Ukraine - M. A. Suchkov (Ибероамериканские тетради, 2023)
Theconflict in Ukraine unfolds at least at three levels– local, international and global. At the same time, the conflict dynamics at all three levels are interconnected, while the interests of external stakeholders directly influence the behavior of local players and determine the prospects for the outcome of the conflict. This article presents Russian assessments of the logic of American policy on the European and Ukrainian tracks in the context of the US attempts to retain the initiative and preserve dominance in international affairs.